2021
DOI: 10.33317/ssurj.362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waste Glass Powder on the Swelling and Strength Characteristic of District Karak Expansive Clay

Abstract: Expansive soils are generally considered problematic due to undesirable geotechnical characteristics like expansion, shrinking, settlement, and heaving. Such soils have low shear strength which decreases after wetting or other physical aggravations. Subsequently, such soils need proper improvement before constructing a structure on them. Different industrial wastes have been used for the stabilization of weak soil in the past. In the current investigation, the impact of waste glass powder (WGP) on the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…This behavior agrees with the findings of several researchers, e.g. Zamin et al (2021) added up to 20% of WGP. The liquid limit dropped from 52.5% to 36%.…”
Section: Atterberg Limitssupporting
confidence: 93%
See 1 more Smart Citation
“…This behavior agrees with the findings of several researchers, e.g. Zamin et al (2021) added up to 20% of WGP. The liquid limit dropped from 52.5% to 36%.…”
Section: Atterberg Limitssupporting
confidence: 93%
“…Another study by Arrieta Baldovino et al (2020) using recycled glass powder to improve silty soil properties in Brazil showed that recycled glass wastes increased durability and strength properties. The study by Zamin et al (2021) showed a reduction in the swelling potentials of waste glass powder modified expansive soils. All the studies mentioned showed the successful application of recycled glass powder as a soil stabilizer in the countries where it was applied.…”
Section: Introductionmentioning
confidence: 96%
“…Pakistan generates a lot of glass waste, which is dumped in fields near the country's manufacturing hubs. The harmful effects on the environment can be mitigated through recycling and the use of the SLGP for soil stabilization [35]. As reported by the Environmental Protection Agency (EPA) of Azad Jammu and Kashmir, about 7 tonnes of waste glass is generated daily across different locations including Mirpur Industrial Area, Jhelum, Bhimber, and Chaksawari region.…”
Section: Testing Program and Methodologymentioning
confidence: 99%
“…The addition of waste glass powder with variations of 0%, 4%, 8%, 12%, 16%, and 20% with expansive soils can increase the specific gravity and maximum dry density values, reduce soil swelling, reduce soil liquid limit values, with optimum variations waste glass powder at 20% variation. [4] The research used steel slag and fly ash, with varying percentages of 0%, 10%, 20%, and 30% steel slag and 0% and 20% fly ash, and curing for 0 days, 3 days, and 7 days. Based on this research, the results obtained a plasticity index of 24.59% and the highest CBR value in the addition of 20% steel slag and 20% fly ash, and 7 days of curing time.…”
Section: Introductionmentioning
confidence: 99%